REKONTRUKSI PERTANGGUNGJAWABAN HUKUM ATAS KERUSAKAN LINGKUNGAN DALAM INDUSTRI TEBU BERBASIS PRINSIP HUKUM EKONOMI SYARIAH - Andi Susanto; Zaini Miftah (KASBANA, 2026)
AbstractThis study examines the reconstruction of legal liability for environmental damage in the sugar industry based on the principles of Islamic economic law. The main issue addressed is the limited effectiveness of the existing environmental legal framework in achieving substantive justice, particularly in addressing ecological damage caused by land-burning practices in agribusiness activities. This study aims to reconstruct the concept of legal liability by integrating the principles of Islamic economic law to establish a more ethical and sustainable legal framework. Unlike previous studies, which primarily examine environmental liability from the perspective of positive law or discuss Islamic economic law in a general normative context, this research offers a novel contribution by developing an integrated legal liability model that combines the principles of maqashid al-shariah, fiqh al-bi'ah, and environmental accountability within a preventive, corrective, and restorative framework. This research employs a normative juridical method using statutory and conceptual approaches, with analysis based on maqashid al-shariah and fiqh al-bi'ah as ethical foundations. The findings reveal that the existing legal liability framework remains predominantly repressive and has not fully accommodated preventive and restorative dimensions. In contrast, Islamic economic law emphasizes moral accountability, the principle of khilafah (stewardship), and the protection of public welfare (maslahah), thereby providing a more comprehensive model of legal responsibility. Based on these findings, this study proposes a reconstructed legal liability model that integrates preventive, corrective, and restorative mechanisms grounded in Islamic principles as a new paradigm for resolving environmental disputes. This model is expected to provide a conceptual contribution to the development of Indonesia's environmental law toward a more just, sustainable, and public welfare-oriented legal system. Keywords: legal liability, environmental damage, sugar industry, Islamic economic law, maqashid al-shariah.